A Rare Case of Herpes Simplex Virus-2 Hepatitis with Negative Serology. (4th June 2019) - Soliman, Mohanad; Akanbi, Olalekan; Almagdub, Ihab; Karri, Kishore; Yarra, Pradeep; Emhmed Ali, Saad; El Haddad, Hanine
Abstract : Herpes simplex virus-2 (HSV2) hepatitis represents a rare but serious complication of HSV2 infection that can progress to acute liver failure (ALF). We describe a case of a pregnant teenager who presented with four days of fever, headache, malaise, nausea, and vomiting. She was initially misdiagnosed with sepsis of unclear source and treated with broad-spectrum antibiotics. Empiric acyclovir was started one week into her hospitalization despite negative serologies while awaiting HSV2 PCR leading to complete resolution of symptoms. Given its high mortality and nonspecific presentation, clinicians should consider HSV hepatitis in all patients with acute hepatitis especially in high-risk population.